2011
DOI: 10.1112/s0010437x11005598
|View full text |Cite
|
Sign up to set email alerts
|

Actions of higher-rank lattices on free groups

Abstract: If G is a semisimple Lie group of real rank at least two and Γ is an irreducible lattice in G, then every homomorphism from Γ to the outer automorphism group of a finitely generated free group has finite image.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…To finish the discussion of Theorem 2.1, we sketch an alternative beautiful argument due to Bridson-Wade [20]. Suppose that φ : Γ → Map(X) is a homomorphism with infinite image.…”
Section: Homomorphisms Between Lattices and Map(x)mentioning
confidence: 99%
See 1 more Smart Citation
“…To finish the discussion of Theorem 2.1, we sketch an alternative beautiful argument due to Bridson-Wade [20]. Suppose that φ : Γ → Map(X) is a homomorphism with infinite image.…”
Section: Homomorphisms Between Lattices and Map(x)mentioning
confidence: 99%
“…In section 2 we discuss a result due to Farb-Masur [29], which states that every homomorphism from a higher rank lattice to Map(X) has finite image, sketching a proof due to Bridson-Wade [20]. We also discuss briefly homomorphisms from Map(X) to lattices, proving for example that, under any such homomorphism, Dehn twists are mapped to roots of unipotent elements.…”
mentioning
confidence: 99%
“…Later, Bridson and Wade [BW11] showed that the same superrigidity remains true if the target group is replaced with Out(F N ), the outer automorphism group of a (non-abelian) free group F N of finite rank N. In an unpublished manuscript of [Mim], the present author obtained a similar homomorphism superrigidity from (commutative) universal lattices and symplectic universal lattices, that means, groups of the form SL(n, Z[x 1 , . .…”
Section: Resultsmentioning
confidence: 99%
“…Remark 1.3. In [BW11], Bridson and Wade defined that a group is Z-averse if no finite index subgroup admits a normal subgroup that surjects onto Z. Then, they showed that for every Z-averse group, the homomorphism superrigidity into MCG(Σ g ) and into Out(F N ) holds true.…”
Section: (I) For Every Acylindrically Hyperbolic Group G Every Groupmentioning
confidence: 99%
“…Right-angled Artin groups (RAAGs) have delivered considerable applications to geometric group theory (two examples are the association with special cube complexes [18] and Bestvina-Brady groups [2]). Another recent area of progress has been the extension of rigidity properties held by irreducible lattices in semisimple Lie groups to involve mapping class groups and automorphism groups of free groups [5,6,17]. In this paper, we look to what extent this phenomenon extends to the automorphism group of an RAAG A Γ , where Γ is the defining graph.…”
Section: Introductionmentioning
confidence: 99%